Film and constitutional controversy : visualizing Hong Kong identity in the age of "one country, two systems" / Marco Wan, The University of Hong Kong. - Wan, Marco (Law in context., 2020)
In modern-day Hong Kong, major constitutional controversies have caused people to demonstrate on the streets, immigrate to other countries, occupy major thoroughfares, and even engage in violence. These controversies have such great resonance because they put pressure on a cultural identity made possible by, and inseparable from, the 'One Country, Two Systems' framework. Hong Kong is also a city synonymous with film, ranging from commercial gangster movies to the art cinema of Wong Kar-wai. This book argues that while the importance of constitutional controversies for the process of self-formation may not be readily discernible in court judgments and legislative enactments, it is registered in the diverse modes of expression found in Hong Kong cinema. It contends that film gives form to the ways in which Hong Kong identity is articulated, placed under stress, bolstered, and transformed in light of disputes about the nature and meaning of the city's constitutional documents.